Influência da concentração sérica de IgG e diferentes protocolos de aleitamento no desenvolvimento de novilhas holandesas no primeiro ano de vida - Ostapechen, Juliandro (2015)
The challenge of keeping the properly development in the Holstein breeders of reposition (HPB) in the initial stages of creation, depends on both the feed management as well the health condition. The management of heifer s creation, during suckling in collective stalls, with automatic feeders enables the search for new nutritional protocols associated to the transfer of the passive immunity (TIP) which are both determining factors to the success of the livestock. Aiming the evaluation of the influence of the IgG serum in the weight gain of heifers during suckling and after their first year of life, it was conducted an experiment with 45 Holstein heifers distributed in three collective stalls equipped with automatic feeders where the heifers were undergone to three different suckling protocols. These protocols were denominated as: treatment one, with the daily provision of 4 liters of milk replacer at ease; treatment two, with the daily provision of 6 liters of milk replacer at ease; and treatment three with the daily provision of milk replacer at ease. All the heifers began the experiment on their fifth day of life and the concentration of serum immunoglobulin G (IgG), was at least 10 mg/dL, with a variation around 13,4 and 43,7 mg/dL. The experimental period of suckling, in all the treatments was fixed in 55 days and all the animals were weaned on their sixth day of life. The heifers had their weight gain checked weekly. After weaned, all the heifers were conducted to a single collective lot and handled under the same feeding conditions until their first year of life. The feeding management in the post-weaning had a daily ingestion of 2kg of supplement divided in 2 meals during the period of 10 months. During this period, they also had Tifton straw at ease and free access to pickets with Tifton grass. After the weaning, the measurement of the body weight of the heifers was taken in monthly intermissions. The experimental design used was totally randomized (DIC). All the data were evaluated by statistics analysis of the linear correlation of Pearson, analysis of variance ANOVA and submitted to the Tukey's average test at 5% and a paired t-test at 5% of significance. Regarding to the performance in the weight gain, there was no influence of the IgG concentration in the weight gain to the weaning and neither in the weight gain after the heifers were one year old. The evaluation of the weight gain occurred between the treatments and disregarding treatments. When dealing with the performance and taking only the suckling protocol, it has been found that the treatments 2 and 3 have shown a higher weight gain at weaning , but the efficiency in weight gain after the heifer's first year was higher in treatments 1 and 3. It was concluded that since the minimum serum concentration of IgG is 10mg/dL, there is no interference of this parameter about the weight gain at weaning and during the first year of life of the heifer. The milk consumption at ease ensures a better weight gain of animals compared to the animals with controlled milk consumption